Numerical Study of Thermal-Hydraulic Performance Improvement of Enhanced Surface Tubes. Issue 2 (19th January 2023) - Santos, Humberto; Li, Wei; Kukulka, David
Abstract: A computational fluid dynamics study was carried out to compare the thermal-hydraulic performance of two enhanced heat transfer tubes (Vipertex models 1EHT-1 and 1EHT-2) to the performance of a smooth surface tube while using R410A as the working fluid. All tubes had an equivalent internal diameter of 8.32 mm and were made of stainless steel. Analysis was performed using an SST (shear stress transport), k-omega numerical model, with the Reynolds number ranging from 15500 to 32500. There was an increase in the heat transfer coefficient and frictional pressure drop for increasing Reynolds number. Heat transfer coefficient relative error (RE) percentage for all tubes evaluated was below 10%, while for the pressure drop the RE was below 16%. Additionally, an analysis of the boundary layer in the case of the enhanced surface tube shows a fluid flow disruption and it reveals increased fluid mixing with enhanced heat transfer. Additionally, it was discovered that dimple height has more of an effect on the thermal hydraulic performance than dimple diameter. It is possible to conclude that the SST k-omega model can be used to simulate and predict heat transfer within an acceptable error tolerance, allowing the optimization of operational parameters.